Literature Review: Innovation in Mathematics Learning through Gamification to Improve Elementary School Students' Learning Outcomes (2015-2025) - Agustin, Lutfia; Widiarti, Nuni; Ellianawati, Ellianawati; Avrilianda, Decky (Jurnal Penelitian Pendidikan, 2025)
Mathematics learning in elementary schools is often considered difficult and uninteresting by students, resulting in low motivation and learning outcomes. To overcome this problem, gamification comes as one of the innovative approaches in learning by integrating game elements such as points, levels, challenges, and rewards into the learning process. This study aims to analyze the effectiveness of gamification in improving mathematics learning outcomes of elementary school students through the Systematic Literature Review (SLR) method. The literature analyzed was sourced from various scientific publications, including journals and conference proceedings published between 2015 and 2025, using databases such as Google Scholar, Crossref, Semantic Scholar, and OpenAlex. The study’s findings indicate that the implementation of gamification, through platforms like Wordwall, Quizizz, Kahoot, and other educational games, has been proven to enhance conceptual understanding, learning motivation, and active student participation in mathematics education. However, the success of gamification implementation is influenced by infrastructure readiness, teachers' digital skills, and appropriate instructional design. Thus, gamification has great potential as a long-term learning strategy that can make math more fun and meaningful for elementary school students.